Identificación de los agentes patógenos Nosema spp. y Acarapis spp., en once unidades apícolas localizadas en los municipios de Cajibío y Popayán del departamento del Cauca (2023)
Bees are essential for ecosystems around the world, thanks to the role they play in the pollination of plants and trees, they contribute to the natural regeneration of forests, their presence improves productive parameters of nearby crops, such as the number of fruits. per plant and their quality. Acarapiosis and Nosemosis are diseases that attack honey bees. They are reported as diseases of economic importance by the World Organization for Animal Health due to the impact they have on bee production. In Colombia, these two diseases are notifiable before the Institute. Colombian Agriculture (ICA). There are few studies carried out in Colombia, three previous investigations were found carried out in the departments of Boyacá, Sucre, Magdalena, Risaralda and Cundinamarca that reported these diseases. This work was first developed in the department of Cauca. The purpose of this study was to identify the presence of the pathogenic agents of Acarapiosis and Nosemosis: Acarapis woodi and Nosema sp. in eleven beekeeping units located in two municipalities of the department of Cauca, taking as reference the methodology described in the Manual of diagnostic tests and vaccines for Terrestrial animals, according to the World Organization for Animal Health (2022), through the use of a stereoscope. Sampling was carried out during the months of April, May and June 2023 and a positive sample for Acarapis woodi was obtained in a beekeeping unit in the municipality of Cajibío with an infestation percentage of 8%